2015
DOI: 10.1007/s10815-015-0606-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple thrombophilic single nucleotide polymorphisms lack a significant effect on outcomes in fresh IVF cycles: an analysis of 1717 patients

Abstract: Purpose The aim of the study is to determine if thrombophilic single nucleotide polymorphisms (SNPs) affect outcomes in fresh in vitro fertilization (IVF) cycles in a large general infertility population. Methods A prospective cohort analysis was performed at a university-affiliated private IVF center of female patients undergoing fresh non-donor IVF cycles. The effect of the following thrombophilic SNPs on IVF outcomes were explored: factor V (Leiden and H1299R), prothrombin (G20210A), factor XIII (V34L), β-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…Two articles [15,20] reported FVL mutation and the result of heterogeneity test was I 2 = 96.0 %, P < 0.00001, and no significant differences (RR = 1.57, 95 % CI 0.47-5.27, P = 0.46) were observed between the two groups. Two articles [18,20] reported PGM mutation and the heterogeneity test results was I 2 = 0.0 %, P = 0.8, and no significant difference (RR = 0.83, 95 % CI 0.64-1.09, P = 0.18) was observed. One study reported FVL/ PGM mutation (RR = 1.14, 95 % CI 0.62-2.12, P = 0.67) and one reported FVL/APCR mutation (RR = 1.30, 95 % CI 1.03-1.63, P = 0.…”
Section: Merging Quantitative Datamentioning
confidence: 92%
See 4 more Smart Citations
“…Two articles [15,20] reported FVL mutation and the result of heterogeneity test was I 2 = 96.0 %, P < 0.00001, and no significant differences (RR = 1.57, 95 % CI 0.47-5.27, P = 0.46) were observed between the two groups. Two articles [18,20] reported PGM mutation and the heterogeneity test results was I 2 = 0.0 %, P = 0.8, and no significant difference (RR = 0.83, 95 % CI 0.64-1.09, P = 0.18) was observed. One study reported FVL/ PGM mutation (RR = 1.14, 95 % CI 0.62-2.12, P = 0.67) and one reported FVL/APCR mutation (RR = 1.30, 95 % CI 1.03-1.63, P = 0.…”
Section: Merging Quantitative Datamentioning
confidence: 92%
“…As shown in Fig. 2, four studies [14,17,19,20] reported MTHFR (C677T) mutation and the results showed that MTHFR (C677T) mutation in inherited thrombophilia was not associated with CPR. The homogeneity analysis (P = 0.52, and I 2 = 0.0 %) and effect size merge (RR = 1.05, 95 % CI 0.97-1.14, P = 0.023) showed that there was no significant difference in MTHFR (C677T) mutation between the mutation group and control group.…”
Section: Merging Quantitative Datamentioning
confidence: 95%
See 3 more Smart Citations